2014
DOI: 10.1155/2014/315843
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-Acetyl-beta-D-glucosaminidase as an Early Marker for Acute Kidney Injury in Full-Term Newborns with Neonatal Hyperbilirubinemia

Abstract: Purpose. To investigate renal function estimated by markers in full-term newborns with hyperbilirubinemia. Methods. A total of 332 full-term newborns with hyperbilirubinemia and 60 healthy full-term newborns were enrolled. Total serum bilirubin, serum creatinine (Cr), serum blood urea nitrogen (BUN), serum cystatin C (Cys-C), urinary beta-2-microglobulin (β 2MG) index, and urinary N-acetyl-beta-D-glucosaminidase (NAG) index were measured before and after treatment. All newborns were divided into three groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The first group is composed of constitutively expressed proximal tubular proteins that are released into urine in response to early AKI. Examples include the lysosomal enzyme N-acetyl b-glucosaminidase (NAG), 1 the cytosolic protein lactate dehydrogenase, 2 or the brush border protein gp330 (previously referred to as the renal tubular epithelial antigen). 3 The second group is composed of tubule "stress molecules," which respond to injury with increased gene transcription (mRNA elevations), protein translation, and ultimately, protein release into the urinary space.…”
mentioning
confidence: 99%
“…The first group is composed of constitutively expressed proximal tubular proteins that are released into urine in response to early AKI. Examples include the lysosomal enzyme N-acetyl b-glucosaminidase (NAG), 1 the cytosolic protein lactate dehydrogenase, 2 or the brush border protein gp330 (previously referred to as the renal tubular epithelial antigen). 3 The second group is composed of tubule "stress molecules," which respond to injury with increased gene transcription (mRNA elevations), protein translation, and ultimately, protein release into the urinary space.…”
mentioning
confidence: 99%
“…11 12 uNAG is valuable in the early detection of AKI, as demonstrated in previous studies. [19][20][21][22][23] Besides, recent studies have indicated that a combination of functional markers and renal tubular damage markers could improve AKI detection in patients with critical illness, 24 25 once again proving the diagnostic value of uNAG. Thyroid disease was thought to be associated with renal disorders and significant changes in renal markers such as creatinine and cystatin C. 26 27 Many studies have suggested that uNAG levels would increase in patients with hyperthyroidism.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Further studies demonstrated an additional benefit of using biomarkers (NGAL, KIM-1, L-FABP) in conjunction with the functional criteria of sCr and urine output, as their combination improves the prediction of worse outcomes [ 155 ]. Other biomarkers are represented by the lysosomal enzyme N-acetyl-b-D-glucosaminidase (NAG) and the cytosolic protein lactate dehydrogenase (LDH) [ 173 , 174 ]. The relationship between NAG and drug-induced kidney disease has been evaluated in several studies [ 135 , 163 , 175 ], focusing mainly on aminoglycoside and cisplatin use, demonstrating that higher NAG levels exhibited a relationship with nephrotoxicity during therapy with aminoglycosides and with a methotrexate and cisplatin combination [ 134 , 135 , 136 ].…”
Section: Biomarker-guided Diagnosismentioning
confidence: 99%